INFLUENCE OF SERVANT LEADERSHIP ON JOB SATISFACTION AND JOB ENGAGEMENT DI CV PANDA FOOD INDUSTRY SIDOARJO - Khafid Khoirul Hanafi; Wahyu Eko Pujianto (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
The purpose of this research was conducted at CV.Panda Food Industry Sidoarjo. The purpose of this study was to determine the effect of servant leadership style on job satisfaction and commitment. The results of the analysis show that concurrent servant leadership has a positive and significant effect on job satisfaction and engagement if the results are treated with a social support beta score of 0.961 sig. 0.000, sign. 0.000 0.05 shows that servant leadership has a significant influence on job satisfaction, while the results of the calculation obtained a self-efficacy beta score of 0.949 sig. 0.000, sign. 0.000 shows that servant leadership has a significant effect on work engagement.